Linguistic development and school adjustment in children in resi-dential care - Moreno Manso, José Manuel; García-Baamonde Sánchez, María Elena; Blázquez Alonso, Macarena (Anales de Psicología / Annals of Psychology, 2010)
The research analyses the communicative competence and the degree of school adjustment of children in care. It provides further knowl-edge of the relationship between the children’s social and linguistic skill and analyses the presence of difficulties in the different components of language (morphology, syntaxis, semantics and pragmatics). The study il-lustrates that the children’s linguistic development is below what is consid-ered to be normal for their chronological age. They have greater difficul-ties in pragmatics and morphology than in syntaxis and semantics. Like-wise, the results indicate that the children present school maladjustment, which demonstrates in aversion to the learning, indiscipline, low motiva-tion and interest for the study, disgust to the teacher and school discon-tent. The research was carried out in children’s homes in Extremadura (Spain). The sample consists of 74 children between 6 and 18 years of age. We call attention to such important aspects as intentionality in communi-cation and the context in which the children’s language is developed.